Students' English Learning Strategies in Dealing with Merdeka Belajar Kampus Merdeka (MBKM) Curriculum in Indonesia: Perceptions and Factors - Sukardi Weda; Geminastiti Sakkir; Andi Elsa Fadhilah Sakti (Hasanuddin University, 2023)
This paper finds the students’ perception students English learning strategies in dealing with Merdeka Belajar Kampus Merdeka (MBKM) curriculum in Indonesia with the research questions: (1) How do students perceive English learning strategies in the current MBKM curriculum change? and (2) What are the supporting factors faced by students in learning English in the current MBKM curriculum change? This study was conducted among all students of the English Education Study Program, Universitas Negeri Makassar, Indonesia in the second, fourth and sixth semesters. From the number of even semester students for the 2021/2022 academic year, which amounted to approximately 500 students, 122 students sent back the results of questions given online. The data obtained from the questionnaire about the student’s perception of the implementation of English learning strategies in the current curriculum change were scored by using the Likert scale. The scoring system was done positively and negatively. The data was analyzed by using percentages. It aimed to measure the respondents’ opinions. Then, to interpret the students’ interest responses, the researchers used the interval estimate. The interval estimation was used to measure the parameter of population based on the score of rates interval sample data and ranged to 5 categories level. The result found that students had a positive perception of English learning strategies in the current curriculum change. This is evidenced by the average student perception score of 68.48 which means it is in a positive category according to the range of perception scores. Therefore, students have a positive attitude to deal with curriculum changes in every era. There were no students who stated very negative statements about the use of learning strategies in the era of curriculum change, there was only 1 student (0.82%) who was very positive. 23 students were hesitant to get a score in the 50-64 interval, and 98 students (80.33%) were in the positive category in the 65-80 interval. Many factors influence students' English learning strategies before and during the Covid-19 Pandemic era. The factors come from students, lecturers, school, environment, learning process and materials conditions.